Synthesis of Aryl-Substituted 3,3a,4,5-Tetrahydropyrrolo[1,2-a] quinolin-1(2H)-ones and 2,3,4,4a,5,6-Hexahydro-1H-pyrido[1,2-a]quinolin-1-ones - Watts, Field M.; Bunce, Richard A. (Synthesis, 2019)
A new route to the title benzo-fused angular tricyclic amides 3,3a,4,5-tetrahydropyrrolo- and 2,3,4,4a,5,6-hexahydro-1H-pyrido[1,2-a]quinolin-1-ones is reported from 1-(tert-butyl) 6-ethyl 3-oxohexanedioate and 1-(tert-butyl) 7-ethyl 3-oxoheptanedioate. Alkylation of these β-keto diesters with a series of 2-nitrobenzyl bromides followed by acid hydrolysis and decarboxylation gives ethyl 6-(2-nitrophenyl)-4-oxohexanoates and ethyl 7-(2-nitrophenyl)-5-oxoheptanoates, respectively. Reductive amination under hydrogenation conditions followed by ester hydrolysis and condensative ring closure affords the final lactam products. The reactions proceed cleanly and only two chromatographic purifications are required.
Keywords: benzo-fused lactams; alkylation–decarboxylation; β-keto diesters; reductive amination; ester hydrolysis; lactamization